Regenerative therapy for the permanent immature teeth: A long term study. An original research - Debkant Jena; P B Sabiha; Neshaneni Satish Kumar; Sanya Syed Ahmed; Priyanka Bhagat; Shobhit Pratap Singh; Mohammed Mustafa (Wolters Kluwer Medknow Publications, 2023)
Introduction: Endodontics faces several clinical difficulties while treating young necrotic permanent teeth. The use of regenerative endodontic procedures (REPs) enables apical closure, improved canal wall thickness, and root growth. The objective of this study was to assess the effects of these regenerative procedures on immature necrotic permanent teeth. Methods: This prospective clinical study was conducted at the tertiary care hospital for the study period of 2 years. This study includes 30 necrotic permanent immature teeth that were studied in 30 subjects of both genders. A standard REP protocol was used to treat every tooth. A follow-up visit was scheduled for each patient at timely intervals. Various study parameters as well as the demographics were assessed at each visit. To examine various parameters, a calibrated endodontist also performed a radiographic evaluation. Results: Our findings point to excellent rates of survival, clinical success, and apical pathological resolution for 29 teeth. After 2 years, there were significant variations in the root thickness area and the average root length. The apical diameter significantly decreased during the research period, with 30.8% of the instances exhibiting full apical closure. Apical diameter, root length, and thickness changed more frequently in teeth with the level of the immaturity of the root, although the variations were not significant. Conclusions: REP treatment for teeth preceded symptom relief. Increased root thickness, root length, and apical closure were seen at 30 months, even if the clinically meaningful change was not attained in all patients.